THE ROLE OF EDUCATORS IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN FORMING THE CHARACTER OF STUDENTS IN ELEMENTARY SCHOOLS - Lulu rohmatun nazilah; Danti Oktarina; Apri Wahyudi (Program Pascasarjana UIN Sumatera Utara, 2024)
This research investigates how teachers play an important role in learning Islamic Religious Education (PAI) in elementary schools in shaping students' characters. The purpose of this study is to discover the problems faced by educators when conveying Islamic religious values. In addition, this study will also investigate effective learning strategies to achieve these goals. The results show that teacher exemplary is the main key in shaping learners' character; teachers not only teach but also act as moral role models. In addition, it is evident that active learning approaches successfully increase students' participation and their understanding of Islamic religious concepts. In addition, this study emphasizes the importance of school, parent and community collaboration in supporting character education. With this collaboration, it is expected that learners can develop good character and become individuals who are ready to face future challenges.